Reliability and validity of the pediatric feeding and swallowing disorders family impact scale for Turkish children with cerebral palsy by endoscopic evaluation - Umay, Ebru; Gündoğdu, İbrahim and Öztürk, Erhan Arif (The Turkish Journal of Pediatrics, 2019)
The caregivers of children with cerebral palsy (CP) have high mood disorders and stress levels. This study was aimed to conduct validity and reliability of Turkish version of The Pediatric Feeding and Swallowing Disorders Family Impact Scale (PFSDFIS) by using an objective method. This study was performed in our physical medicine and rehabilitation (PMR) clinic between July 2016 and July 2018. This study was performed with 251 children with CP who had complaint of swallowing and/or feeding problems, and their primer caregivers. Cronbach`s alpha and corrected item-total correlations were used to assess internal consistency. Test and retest reliability studies were also conducted. The construct validity was assessed using the dysphagia level defined with flexible fiberoptic endoscopic evaluation of swallowing and Impact on Family Scale (IFS). Total score of T-PFSDFIS was correlated to the dysphagia level by using FEES. Results showed, Cronbach’s alpha value of the scale to be 0.821. Corrected item-to-total correlations ranged from 0.729 to 0.911. Test-retest reliability coefficients was calculated with intra-class correlation coefficient (ICC), the total score was 0.989. A negative significant good level correlation was found between the dysphagia level by using endoscopic evaluation and the T- PFSDFIS total score as well as between total scores of IFS and T-PFSDFIS. In subgroup analysis; the lowest value was in normal swallowing and significantly different from all dysphagia levels. In conclusion; this scale is effective in reflecting the influence of caregivers on the severity of dysphagia measured objectively and T-PFSDFIS is a valid and reliable scale for Turkish children with CP.